Efektivitas penggunaan model pembelajaran problem posing terhadap peningkatan kemampuan berpikir kritis mahasiswa - Ratna Rustina (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
This research was conducted to provide alternative learning models that can improve the ability of students’ reasoning. By giving the opportunity to students to be more active in the learning process, Problem Based Learning model was one of the alternatives to improve students’ reasoning in calculus III courses. This research was quasi-experimental research at the Siliwangi University Tasikmalaya. The instruments used in this study consists of mathematical reasoning tests in Calculus III. Research samples were taken randomly i.e. one experimental class and one control class. Data processed by using the normalized gain test, t-test percentage presentation after all the requirements of the test were met. The results of the analysis showed a difference of the average of students’ mathematical critical thinking between experiment and control class. Further test showed that students’ average of experiment class was better than the control class.